Ciswak Ritual as a Ritual of Rejecting the Annual Bala of the Chinese - Atik Febriyani (Bambuti, 2022)
This article discussed the ciswak ritual at a temple in the Chinatown area of ​​Semarang, namely the Sinar Samudra Temple. Ciswak is a ritual of rejecting reinforcements performed by the Chinese every year to protect themselves from bad things. The research methodology and data collection technique are qualitative in collecting data through direct interviews and field research. Field research was carried out from a few days before the ritual until the ciswak ritual was completed using a descriptive analysis design. The Chinese consider that if the ciswak ritual is performed solemnly in both reading prayers and ritual movements and including repentance, which is carried out all day long, then this aims to show the sincerity of humans to want to receive protection and blessings from the gods and avoid away from evil and danger. This ritual is not only because one's birth sign is Chiong( bad luck) in that year, it is also because of the belief to carry out the ritual of repelling reinforcements every year even though the birth sign is not chiong. Chinese people in Semarang still strongly believe in the values ​​of ancestral heritage in the teachings of Taoism